Predicting L2 reading proficiency with modalities of vocabulary knowledge: A bootstrapping approach. (July 2020) - McLean, Stuart; Stewart, Jeffrey; Batty, Aaron Olaf
Vocabulary's relationship to reading proficiency is frequently cited as a justification for the assessment of L2 written receptive vocabulary knowledge. However, to date, there has been relatively little research regarding which modalities of vocabulary knowledge have the strongest correlations to reading proficiency, and observed differences have often been statistically non-significant. The present research employs a bootstrapping approach to reach a clearer understanding of relationships between various modalities of vocabulary knowledge to reading proficiency. Test-takers ( N = 103) answered 1000 vocabulary test items spanning the third 1000 most frequent English words in the New General Service List corpus (Browne, Culligan, & Phillips, 2013). Items were answered under four modalities: Yes/No checklists, form recall, meaning recall, and meaning recognition. These pools of test items were then sampled with replacement to create 1000 simulated tests ranging in length from five to 200 items and the results were correlated to the Test of English for International Communication (TOEIC®) Reading scores. For all examined test lengths, meaning-recall vocabulary tests had the highest average correlations to reading proficiency, followed by form-recall vocabulary tests. The results indicated that tests of vocabulary recall are stronger predictors of reading proficiency than tests of vocabulary recognition, despite the theoretically closer relationship of vocabulary recognition to reading.